Simulation Model and Practical Testing of Operating Characteristic of ‎Differential Protection for Optimization of Fault Discrimination of Power ‎Transformer (Journal of University of Babylon for Engineering Sciences, 2025)
Differential protection is a key technique used to safeguard power transformers from internal faults while ensuring stable operation during inrush currents and external faults. The objective of this study is to evaluate the operating characteristic curve of differential protection by the simulation model enabled various fault scenarios, including magnetizing inrush currents, external faults, and internal faults. A differential protection model for a three-phase transformer was simulated using MATLAB/Simulink to simulate various fault conditions and also present a practical test was conducted using an Omicron CMC 356 tester tuned to the proposed curve to validate the relay's performance under controlled experimental conditions, which addresses the lack of experimental validation for differential protection under combined fault scenarios. The same fault types and parameters were used in both Simulink and Omicron CMC 356 tests, producing identical detection results with a 30 ms trip time. The experimental results closely align with those obtained from the simulation, confirming that the proposed differential protection operating characteristic curve is more stable when distinguishing external faults and inrush currents, and performs more efficiently when distinguishing internal faults. Combining real-time MATLAB/Simulink and CMC 356 experiments provides an effective methodology for validating the proposed differential protection technology for power transformers.